Maintenance of high-rise residential buildings - Chua, Shirley Jin Lin; Zubbir, Najilah; Ali, Azlan Shah; Au-Yong, Cheong Peng (Emerald, 2018)
Purpose: Preventive maintenance is an effective maintenance strategy to ensure the constant and efficient usage of building systems and their components. The reactive-based maintenance as the main strategy in high-rise residential buildings is a concern as the maintenance output resulting from the strategy could not achieve the standard level of performance. The purpose of this paper is to identify the characteristics of preventive maintenance and establish the relationship with maintenance performance in high-rise residential buildings. Design/methodology/approach: The characteristics of preventive maintenance and maintenance performance parameters were identified through the literature review. A quantitative approach was adopted, where a questionnaire was distributed to the maintenance personnel of high-rise residential buildings. Then, ranking analysis and correlation were conducted to produce findings that help to achieve the research objectives. Findings: The research findings indicate that there are seven maintenance characteristics significantly correlated with maintenance performance indicators (maintenance costs deviation, time variance of maintenance work, customer service and downtime rate). It is recommended that these characteristics are considered during the execution of preventive maintenance as they have a significant effect on the maintenance performance. Originality/value: The extensive literature suggests the relationship between the characteristics of preventive maintenance and maintenance performance, but is still questionable. Thus, this research investigates the relationship between preventive maintenance characteristic and maintenance performance for high-rise residential buildings in Malaysia. The findings of the research can act as a guide for maintenance personnel to optimise maintenance performance by focusing on the highlighted preventive maintenance characteristics.